Habbatussauda dalam Peningkatan Imun di Masa Covid-19 - Muhamad Ikhsan (Jurnal Riset Agama, 2021)
The purpose of this study is to discuss the hadith of Black Seed as an alternative in increasing immunity during the Covid-19 period. This research uses a qualitative approach through literature study by applying the method of takhrij hadith and syarah hadith. The interpretation is used to analyze contemporary issues. The results of the research and discussion show that the hadith about Black Seed as one of the authentic quality herbal treatments according to takhrij reviews so that it can be practiced as an Islamic argument. While the syarah of this hadith shows that Black Seed is used for the treatment of various diseases, moreover it is very useful for increasing one's body immunity, however this Black Seed also cannot absolutely be interpreted to treat all diseases, especially Covid-19, further research is needed on this matter. The conclusion of this study is that the hadith about Black Seed is maqbul for herbal treatment, but with the right rules and doses and it is even better if it is under the supervision of the relevant experts, namely health experts.